2022
DOI: 10.3390/nu14132704
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 on Nutritional Intake in Rural China: Panel Data Evidence

Abstract: The COVID-19 pandemic introduced risks and challenges to global food and nutrition security. In this paper, we examine the impact of the COVID-19 pandemic on the nutritional intake of China’s rural residents using panel data and a fixed effects model. The data were collected in 2019 and 2020 and covered nine provinces and 2631 households in rural China. The results reveal that an increase of 100 confirmed cases in a county resulted in a 1.30% (p < 0.01), 1.42% (p < 0.01), 1.65% (p < 0.01), and 1.15% (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…There were other reasons for the higher mortality in rural areas, such as nutrient intake. Data collected in rural China revealed that an increase of 100 confirmed cases in a county resulted in a 1.30%, 1.42%, 1.65%, and 1.15% decrease in per capita intake of dietary energy, carbohydrates, fats, and proteins, respectively [24] . Patient with T2DM who coexisted with CVD and DN, probably had difficulties in glycemic control or progress to a serious state, and subsequently led to they tend to the hesitancy of vaccination and impair the immune defense.…”
Section: Discussionmentioning
confidence: 99%
“…There were other reasons for the higher mortality in rural areas, such as nutrient intake. Data collected in rural China revealed that an increase of 100 confirmed cases in a county resulted in a 1.30%, 1.42%, 1.65%, and 1.15% decrease in per capita intake of dietary energy, carbohydrates, fats, and proteins, respectively [24] . Patient with T2DM who coexisted with CVD and DN, probably had difficulties in glycemic control or progress to a serious state, and subsequently led to they tend to the hesitancy of vaccination and impair the immune defense.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, the COVID-19 pandemic could have different effects on energy and macronutrient intake, which could be due to changes in food consumption patterns as a result of the pandemic [ 53 ]. Since meat and grains are sources of protein and carbohydrates in the diet of Iranians [ 22 , 54 ], protein consumption increased due to the increase in meat consumption in urban and rural areas, and changes in carbohydrate consumption were due to changes in grain consumption in urban and rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that the pandemic could have different effects on energy and macronutrient intake in SES categories, which could be due to changes in food consumption patterns as a result of the pandemic [ 53 ]. Also, studies reported that food consumption decreased during the pandemic [ 16 , 53 ], which could explain the decrease in energy in different SES categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset included 16,613 rural households from eight provinces (Hebei, Jilin, Fujian, Shandong, Henan, Yunnan, Shaanxi, and Xinjiang), 30 counties, and 295 villages ( Figure 1 ). The data recorded the food consumption and food expenditure of the sampled households over a whole year [ 51 , 52 ].…”
Section: Materials and Methodsmentioning
confidence: 99%